Emotion Recognition Based on Dynamic Energy Features Using a Bi-LSTM Network - Zhu, Meili; Wang, Qingqing; Luo, Jianglin (Frontiers in Computational Neuroscience, 2022)
Among EEG signal emotion recognition methods based on deep learning, most methods have difficulty training a high-quality model due to the low-resolution and the small sample size of EEG images. To solve this problem, this paper proposes a deep network model based on dynamic energy features. In this method, first, to reduce the noise superposition caused by feature analysis and extraction, the concept of an energy sequence is proposed. Second, to obtain the feature set reflecting the time persistence and multicomponent complexity of EEG signals, the construction method of the dynamic energy feature set is given. Finally, to make the network model suitable for small datasets, we use fully connected layers and bidirectional long short-term memory (Bi-LSTM) networks. To verify the effectiveness of the proposed method, we use LOSO and 10-fold CV strategies to carry out experiments on the SEED and DEAP datasets. The experimental results show that the accuracy of the proposed method can reach 89.42% (SEED) and 77.34% (DEAP).